Degradation phenomena in Praseodymium Oxide-based Zinc Oxide varistor ceramics derived-through modified citrate technique - Wan Abdullah @ Wan Abd. Rahman, Wan Rafizah (2014)
Current trend shows that Pr6O11 based ZnO ceramics are actively researched to overcome drawbacks in Bi2O3 based varistor materials. However, very little attention has been paid to evaluate the stability of these materials against DC degradation which causes reduction of device lifetime and poses safety risks to users. DC degradation characteristics of four series of Pr6O11 type ceramics prepared through modified citrate gelation technique and solid state sintering are therefore investigated. The series are System 1 (ZnO + Pr6O11), System 2 (ZnO + Pr6O11 + Co3O4), System 3 (ZnO + Pr6O11 + MnO2) and System 4 (ZnO + Pr6O11 + Cr2O3). The objectives of the present study were to determine the microstructure and nonlinear properties as a function of dopant contents and sintering conditions, to evaluate the degradation effects due to simultaneous DC electrical field and high temperature stresses on nonlinear properties of respective varistor system and to investigate the influence of deep levels on varistor degradation by using deep level transient spectroscopy (DLTS) technique. The ceramics were characterized in terms of microstructure profiles, electrical field-current density characteristics, DC degradation behaviour and deep level characteristics. Several important findings of the study are highlighted. PrCrO3 spinel has been developed in varistor ceramics doped with 0.8 mol% Pr6O11 and 1.0 mol% Cr2O3. To certain extent, Pr6O11 and Cr2O3 suppress grain growth. The average grain size, d and average relative density, ρrel decreased with increasing Pr6O11 and Cr2O3 contents. Co3O4 and MnO2 promoted grain growth and densification. Therefore, the d and ρrel values increased with their increasing contents. Electrically, Pr6O11 served as grain boundary activator whereas Co3O4, MnO2 and Cr2O3 further enhanced the nonlinearity. The nonlinear coefficient, α and breakdown field, Eb values increased and the leakage current density, JL value decreased up to certain extent of dopant contents. In the temperature range of 1200 to 1275 oC, most systems demonstrated that d and ρrel values improved with increasing sintering temperature. Similar trend was observed when the sintering time was varied between 1 to 7 hours. Nonlinear properties were improved with increasing sintering temperature and time until an optimum point was reached. Extreme sintering temperature and extended sintering time deteriorate nonlinear characteristics. Ceramics with the highest ρrel value (97.88 + 0.28 %) were obtained from System 1. The ceramics were doped with only 0.2 mol% Pr6O11 and sintered at 1225 oC for 1 hour. Ceramics with the largest d value (18.62 + 4.16 μm) were identified in System 2 which contained 0.8 mol% Pr6O11 and 0.4 mol% Co3O4. They were sintered at 1250 oC for 3 hours. The most pronounced nonlinearity was observed in ceramics of System 4 which were doped with 0.8 mol% Pr6O11 and 0.6 mol% Cr2O3. The corresponding ceramics have been sintered at 1200 oC for 1 hour and demonstrated the α value of 6.04. + 0.02,the Eb value of 127.05 + 0.38 V/mm and the JL value of 327.+.1.μA/cm2. All systems degraded under three stages of stress conditions. At each stage, DC electrical field of 85% from the breakdown field was applied for 18 hours whereas the temperature was increased from 30 to 60 and 125 oC in the subsequent stages. The signs of degradation included a decrease in the α value, the shifting of Eb value to a lower field and a rise in the JL value. Ceramic of System 4 demonstrated the best tolerance to DC degradation compared to the rest by exhibiting %ΔEb value of -9.86%, the %Δα of -4.37% and the %ΔJL of +13.73%. Comparatively, some Pr6O11 based ZnO varistor ceramics obtained in this study exhibited better stability against DC electrical field and temperature stress than the more complex Bi2O3 based ZnO ceramics prepared through similar citrate gel method. As previously reported, chemically derived Bi2O3 based ZnO ceramics that have been doped with more additives such as Sb2O3, MnO, Al2O3, Co2O3,NiO, Cr2O3 demonstrated the %ΔEb value of 1.5%, %Δα of up to -37.5%, and the %ΔJL of +323% when subjected to comparable three stages of DC electrical field and high temperature stresses. DLTS technique confirmed the presence of four electron traps in Pr6O11 based ceramics. The bulk trap, L1 and L2 respectively located (0.09 - 0.15 eV) and (0.29 - 0.39 eV) below the conduction band edge. They were associated to intrinsic donor defects (Vo and Zni) or the complex with extrinsic donor defects (Mn or Co). The interface states, L3 and/or L4 located between 0.45 to 0.91 eV below the conduction band edge and they were associated to defect clusters of zinc vacancy, VZn, adsorbed or chemisorbed oxygen and impurities (Pr, Mn or Co). In degraded state, the densities of L1 and L3 traps for System 1 and 4 have reduced due to annihilation of defects and desorption of oxygen from grain boundary during stress application. The L3 trap in System 4 shifted to a higher energy because of new defect clusters formation. In System 2 and 3, the density of L1 trap increased after degradation test due to an increase in intrinsic defects such as Vo and Zni and extrinsic donor defects in depletion regions. It was accompanied by an increase in density of L3 (System 2) and L4 (System 3) traps which was associated to ionization of mid-gap states induced by Co or Mn. In conclusion, degradation of Pr6O11 based ZnO varistor ceramics which were doped with transition metal oxide (Co3O4, MnO2 or Cr2O3) and derived from modified citrate gel technique due to prolonged DC electrical field and high temperature stresses was a direct effect to Double Schottky Barrier deformation. The degradation mechanisms weregoverned by electromigration and oxygen desorption processes which induced by chemical and electronic changes centering at grain boundary interface.